2013
DOI: 10.1088/0004-637x/770/2/108
|View full text |Cite
|
Sign up to set email alerts
|

HOST GALAXY PROPERTIES AND HUBBLE RESIDUALS OF TYPE Ia SUPERNOVAE FROM THE NEARBY SUPERNOVA FACTORY

Abstract: We examine the relationship between Type Ia Supernova (SN Ia) Hubble residuals and the properties of their host galaxies using a sample of 115 SNe Ia from the Nearby Supernova Factory (SNfactory). We use host galaxy stellar masses and specific star-formation rates fitted from photometry for all hosts, as well as gas-phase metallicities for a subset of 69 star-forming (non-AGN) hosts, to show that the SN Ia Hubble residuals correlate with each of these host properties. With these data we find new evidence for a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
203
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(240 citation statements)
references
References 117 publications
34
203
3
Order By: Relevance
“…5.2.2 we show how this peculiar structure introduces the brightness offset observed between SNe in low-and highmass hosts. This "mass step" is seen in our sample (Childress et al 2013a), as well as in all other large surveys (Kelly et al 2010;Sullivan et al 2010;Gupta et al 2011;Johansson et al 2013). This suggests that this bimodality is not exclusive to the SNfactory data, but is an intrinsic property of SALT2-calibrated SNe Ia.…”
Section: Corrected Hubble Residual Distributionssupporting
confidence: 86%
See 2 more Smart Citations
“…5.2.2 we show how this peculiar structure introduces the brightness offset observed between SNe in low-and highmass hosts. This "mass step" is seen in our sample (Childress et al 2013a), as well as in all other large surveys (Kelly et al 2010;Sullivan et al 2010;Gupta et al 2011;Johansson et al 2013). This suggests that this bimodality is not exclusive to the SNfactory data, but is an intrinsic property of SALT2-calibrated SNe Ia.…”
Section: Corrected Hubble Residual Distributionssupporting
confidence: 86%
“…This has been modeled as either a linear trend or a sharp step in corrected Hubble residuals between low-and high-mass hosts. In Childress et al (2013a) we established that a "mass step" at log(M/M ) = 10.2 gives a much better fit than a line, and we found that the RMS width of the transition is only 0.5 dex in mass. Because the mass of a galaxy correlates with its metallicity, age, and sSFR (see Tremonti et al 2004;Gallazzi et al 2005;Pérez-González et al 2008, respectively), this mass step is most likely driven by an intrinsic SN progenitor variation.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…This could be a reflection of dust, age, and/or metallicity in the progenitor systems (Childress et al 2013b).…”
Section: Dependence On Host Galaxy Massmentioning
confidence: 99%
“…This time-independent color variation encompasses both intrinsic color differences and those due to dust in the host galaxy. It is possible that the color correction varies with redshift, as a consequence of evolution of the progenitor and/or changes in the environment, for example, variation in the dust composition with galactic evolution (Childress et al 2013b). Redshift-dependent dust extinction can lead to biased estimates of cosmological parameters (Menard et al 2010a(Menard et al , 2010b.…”
Section: Redshift Evolution Of the Color Correctionmentioning
confidence: 99%